2019
DOI: 10.1504/ijsnet.2019.097558
|View full text |Cite
|
Sign up to set email alerts
|

A portable roadside vehicle detection system based on multi-sensing fusion

Abstract: To improve traffic efficiency, the intelligent transportation system (ITS) is widely used in urban roads. The sensing system is preferred to be deployed at roadside because the normal traffic would not be interfered. In the field of the magnetic vehicle detection, one of the most challenging problems is the disturbance from the other lane. Most existing magnetic detection systems need more than one magnetic sensor to solve the disturbance. This paper proposes a portable roadside vehicle detection system based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Figure 1 shows an example of before-and-after background filtering. The previous studies [33][34][35] showed that 3D-DSF can exclude more than 95% of background points from the raw LiDAR data.…”
Section: Background Filteringmentioning
confidence: 99%
“…Figure 1 shows an example of before-and-after background filtering. The previous studies [33][34][35] showed that 3D-DSF can exclude more than 95% of background points from the raw LiDAR data.…”
Section: Background Filteringmentioning
confidence: 99%
“…It is connected to a field computer through a router with Ethernet cables. The real-time traffic signal information can be read from conventional traffic controllers through the national transportation communications for ITS protocol (NTCIP) [16]. New traffic signal controllers directly provide SPaT messages, such as the Trafficware 980ATC TS-2 Type 2 Signal Controller.…”
Section: A Roadside Systemmentioning
confidence: 99%
“…In fact, a large amount of research has been done to process LiDAR data under severe weather conditions [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Wojtanowski et al [ 22 ] found that LiDAR is susceptible to adverse weather conditions.…”
Section: Introductionmentioning
confidence: 99%